Integrating scientometric and systematic approaches to explore banana peduncle fibre valorization research insights from 2014 to 2024 - Shibu Comath; Alex Kunnathu George (Discover Sustainability)
Abstract Agricultural biomass waste, like banana peduncle (BP), is gaining attention as a sustainable alternative to non-renewable resources. This study combines scientometric and systematic analyses (2014–2024) to assess BP fibre valorization trends. Following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses, 2020) guidelines, a comprehensive literature search identified 264 research reports through databases (Scopus and Web of Science). These were screened via Rayyan software and inclusion and exclusion criteria, resulting in 127 records for scientometric analysis via VOSviewer software. Among these, 112 reports were analysed to evaluate product properties, processing techniques, and potential applications. The results indicate that India is the leading contributor (35%), followed by Ecuador (11%), in BP fibre valorization research, with strong collaborations with Germany. India’s leadership is attributed to its abundant banana waste and research infrastructure. Research spans Energy and Materials Science, highlighting the potential of BP fibres as a sustainable resource for biofuels, composites, biochar, and advanced biomaterials. Recent trends have focused on bioenergy, bioactive compounds, and nanocellulose production. However, industrial-scale feasibility, production-consumption optimisation, and environmental impact studies remain gaps. This study underscores the need for continued efforts to realise the full potential of BP as a sustainable and versatile material. Graphical abstract